FACE THREATENING ACT STRATEGIES IN JERRY SEINFELD’S I’M TELLING YOU FOR THE LAST TIME STAND-UP COMEDY SHOW - NOVIADHISTA, ULWAN FAKHRI (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Politeness, Face, Face Threatening Act (FTA), Stand-up Comedy.Face threatening act (FTA) is inseparable from verbal communication. As a result, both speaker’s and the hearer’s faces are in danger. This leads to a huge problem for stand-up comedians, who only rely on verbal jokes to make their audiences listen and pay attention. The writer then chooses Jerry Seinfeld, an American stand-up comedian whose genre is observational comedy, as the object of this study. This study aims to find out what strategies that are performed by Jerry Seinfeld in his stand-up comedy show entitled I’m Telling You for The Last Time in threatening his and the audiences’ faces.Qualitative approach is used in this study to collect and examine the data. In addition, this study applies document analysis to analyze and interpret the utterances produced by Jerry Seinfeld that contain face threatening acts and their strategies based on the face threatening act strategies theory proposed by Brown and Levinson (1987).The findings of this study reveal that all face threatening strategies are used by Jerry Seinfeld in his act, with domination in strategies with redressive actions, in particular negative politeness strategy. This strategy is more exploited as he wanted to respect his hearers’ want to stay free and be funny by stating his own insights inside his jokes at the same time. Moreover, the least used strategy is bald on record, as it is too unsafe to state opinions without softening the speaker’s intention. This indication shows that in his comedy performance, the stand-up comedian still considers respecting his own and audiences’ faces when he performs verbal communication through his jokes.Based on the results, the writer suggests that the next researchers analyze different genre, gender, or nationality of various stand-up comedians on how they perform their face threatening act strategies in their comedy performance.